Rethinking Uncle Tom : the political philosophy of Harriet Beecher Stowe - Allen, W. B. (William Barclay), 1944- (Lexington Books, 2009)
Generally critics and interpreters of Uncle Tom have constructed a one-way view of Uncle Tom, albeit offering a few kind words for Uncle Tom along the way. Recovering Uncle Tom requires re-telling his story. This book delivers on that mission, while accomplishing something no other work on Harriet Beecher Stowe has fully attempted: an in-depth statement of her political thought. Heroeuvre, in partnership with that of her husband Calvin, constitutes a demonstration of the permanent necessity of moraland prudential judgment in human affairs. Moreover, it identifies the political conditions that.